Self-Esteem and Self-Efficacy of Students' Attending Online Courses Through MBKM Program - Sahril Nur; Nofvia De Vega; Anugrah Puspita Ayu Muhammad (Journal of Educational Science and Technology (EST), 2022)
This study aims to analyze the students’ self-esteem and self-efficacy attending online courses of an MBKM exchange program. It was organized by three participating universities using SPADA DIKTI. Quantitatively, the study employed an online questionnaire to collect the data from 80 participating students (N=80). The statistical analysis, which included multiple regression analysis, was performed using SPSS 26. The findings indicate that the variables self-esteem and self-efficacy have a significant and beneficial effect on students enrolled in concurrent online courses. Statistically, the study used an F test and a T-test to identify the considerable impact of the measured variables. The results show that both variables have a substantial and beneficial impact on students enrolled in concurrent online courses. The students’ self-esteem excels academically, primarily through the online teaching and learning system. Meanwhile, the students with mastery experience subcomponents accepted new challenges and succeeded in doing them. Based on hypothesis testing, there is a significant effect between self-esteem and self-efficacy on students who attended online courses, which amounted to 48.9%. Yet, self-esteem and self-efficacy regression coefficients also positively affect online lectures.